1995
DOI: 10.1073/pnas.92.12.5550
|View full text |Cite
|
Sign up to set email alerts
|

Operational RNA code for amino acids: species-specific aminoacylation of minihelices switched by a single nucleotide.

Abstract: The genetic code is based on aminoacylation reactions where specific amino acids are attached to tRNAs bearing anticodon trinucleotides. However, the anticodonindependent specific aminoacylation of RNA minihelix substrates by bacterial and yeast tRNA synthetases suggested an operational RNA code for amino acids whereby specific RNA sequences/structures in tRNA acceptor stems correspond to specific amino acids. Because of the possible significance of the operational RNA code for the development of the genetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 19 publications
3
50
0
Order By: Relevance
“…These results are in good agreement with previously published comparisons between bacterial and eukaryotic tyrosyl-tRNA synthetases (17)(18)(19)(20)(21). Similar species specificity has also been observed for several other aminoacyl-tRNA synthetases (55)(56)(57)(58)(59) and is consistent with the hypothesis that the recognition of tRNA by aminoacyl-tRNA synthetases was still evolving after the divergence of bacteria and eukaryotes (39). The observation that tyrosyl-tRNA synthetase from the archaeon M. jannaschii lacks a substantial portion of the tRNA anticodon recognition domain suggests that the archaea may recognize and bind tRNA Tyr in a manner distinct from that found in both bacteria and eukaryotes.…”
Section: Resultssupporting
confidence: 82%
“…These results are in good agreement with previously published comparisons between bacterial and eukaryotic tyrosyl-tRNA synthetases (17)(18)(19)(20)(21). Similar species specificity has also been observed for several other aminoacyl-tRNA synthetases (55)(56)(57)(58)(59) and is consistent with the hypothesis that the recognition of tRNA by aminoacyl-tRNA synthetases was still evolving after the divergence of bacteria and eukaryotes (39). The observation that tyrosyl-tRNA synthetase from the archaeon M. jannaschii lacks a substantial portion of the tRNA anticodon recognition domain suggests that the archaea may recognize and bind tRNA Tyr in a manner distinct from that found in both bacteria and eukaryotes.…”
Section: Resultssupporting
confidence: 82%
“…It is possible in vitro to alter a tRNA's amino acid charging identity by anticodon mutations (Schulman and Pelka 1989;Pallanck and Schulman 1991). It has also been shown that mutations outside the anticodon, for example, involving acceptor stem nucleotides that are strong identity determinants, can also effectively switch the identity of a tRNA (Hipps et al 1995). That "identity switches" could potentially occur by single or a few mutations was first demonstrated in vivo by the rescue of an inviable tRNA-Thr(UGU) deletion mutant of E. coli by a mutant tRNA-Arg(UGU) gene (Saks et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that some tRNAs have different identity rules in different taxa. For example Escherichia coli tRNA-Gly uses a crucial U73 discriminator base in combination with a C2:G71 pair, while in mammals the discriminator base is A73 (Shiba et al 1994;Hipps et al 1995); prokaryotic tRNA-Asp uses a U73 and the first base pair G1:C72 of the stem, while eukaryotes use A73 and the third base pair of the stem (Nameki et al 1992. Although crucial to our understanding of the evolution of the genetic code (Schimmel et al 1993), the evolution of tRNA identity elements has been the subject of few studies.…”
Section: Introductionmentioning
confidence: 99%
“…We also considered that the evolution of a synthetase is codeveloped with the evolution of tRNA determinants that are necessary for the enzyme to aminoacylate its tRNA. The codevelopment of a synthetase with its cognate tRNAs is necessary for the preservation of the genetic code and is supported by studies of various tRNA-synthetase interactions (7)(8)(9)(10)(11)(12). Thus, the E. coli enzyme has developed to recognize tRNA determinants of E. coli tRNA Cys , while the yeast enzyme has developed to recognize determinants of yeast tRNA Cys .…”
mentioning
confidence: 99%